Enforcing Law Through Authoritarian Environmentalism? State and Non-State Actors in China's Environmental Public Interest Litigation - Yi Ma; Wen Xiang (Journal of Current Chinese Affairs, 2023)
Numerous studies have examined China's authoritarian environmentalism, with a focus on policy-making and implementation. We argue that law enforcement should also be investigated as a crucial stage. Specifically, we examine environmental public interest litigation (EPIL) and analyse a novel dataset of 7010 EPIL court judgements from 2015 to 2020. We find that state prosecutors dominate EPIL activities, while the role of non-governmental organisations (NGOs) is strictly limited. We also show great variations in EPIL lawsuits filed by state prosecutors across provinces, indicating high local discretion over environmental law enforcement. Lastly, we doubt whether the great number of EPIL outputs from state prosecutors will produce significant environmental outcomes, because they tend to target low-hanging fruit, in contrast to the more challenging and environmentally profound EPIL cases initiated by NGOs. We highlight the value of using the authoritarian environmentalism framework to contextualise debates surrounding the development of EPIL in China.